Evaluation of air pollution by PM10 and SO2 levels in Erzurum province, Turkey: Descriptive study - Koşan, Zahide; Kavuncuoğlu, Duygu; Çalıkoğlu, Elif Okşan; Bilge Yerli, Ezel (Journal of Surgery and Medicine, 2018)
Aim: Air pollution is an important, global, health-threatening environmental risk factor. Air pollution can cause potentially fatal respiratory tract and other diseases. Erzurum is the largest and most developed city in northeast Turkey. The purpose of this study was to determine levels of air pollution in the center of Erzurum province in 2012 and 2017. Methods: Data for the Erzurum station for July 2012-July 2017 in this cross-sectional descriptive study were obtained from the Turkish Ministry of the Environment and Urban Planning Air Quality Monitoring Stations web site. The data obtained were compared with European Union (EU) Countries, World Health Organization (WHO) and Turkish national threshold values. Descriptive statistics were expressed as median, minimum-maximum value and percentage, Kruskal Wallis and Mann Whitney U tests were used in the analysis. Results: At the Erzurum station, the PM10 (particles less than 10 microns) median value for the years 2012-2017 was 27 (min: 2; max: 443), the SO2 median value was 6 (min: 0; max: 443). PM10 exceeded the Turkish national limit on 22 days in 2012; 37 in 2013; 23 in 2014; 40 in 2015; 74 in 2016; and 27 in 2017. SO2 did not exceed the Turkish national limit on any days in 5 years. SO2 (sulfur dioxide) exceeded the WHO limits on 3 days in 2012, 30 in 2013, 42 in 2014, 56 in 2015, 37 in 2016 and none in 2017. Statistical analysis revealed that PM10 and SO2 values varied significantly by year (p<0.001), season (p<0.001) and month (p<0.001). The values for both parameters were higher in winter, and the highest median values occurred in January. Conclusion: The problem of air pollution in Erzurum has decreased compared to previous years, but it still not at recommended levels.